Vitamin D and chronic kidney disease - Kim, Chang Seong (The Korean Association of Internal Medicine, 2014)
Chronic kidney disease (CKD) has been recognized as a significant global health problem because of the increased risk of total and cardiovascular morbidity and mortality. Vitamin D deficiency or insufficiency is common in patients with CKD, and serum levels of vitamin D appear to have an inverse correlation with kidney function. Growing evidence has indicated that vitamin D deficiency may contribute to deteriorating renal function, as well as increased morbidity and mortality in patients with CKD. Recent studies have suggested that treatment with active vitamin D or its analogues can ameliorate renal injury by reducing fibrosis, apoptosis, and inflammation in animal models; this treatment also decreases proteinuria and mortality in patients with CKD. These renoprotective effects of vitamin D treatment are far beyond its classical role in the maintenance of bone and mineral metabolism, in addition to its pleiotropic effects on extra-mineral metabolism. In this review, we discuss the altered metabolism of vitamin D in kidney disease, and the potential renoprotective mechanisms of vitamin D in experimental and clinical studies. In addition, issues regarding the effects of vitamin D treatment on clinical outcomes are discussed.